Numerical assessments of flow pattern and heat transfer profile for the round tube equipped with different configurations of the dual-inclined baffle - Boonloi, Amnart; Jedsadaratanachai, Withada (My University, 2021)
Numerical studies of the heat exchanger tube (HXT) equipped with the dual-inclined baffle (DIB) on fluid streams and heat transfer profiles are reported. The DIB configurations can be separated into three types: 1. The DIB is inserted in the middle of the HXT called “type I″, 2. The DIB is placed on the HXT wall called “type II” and 3. The combination of the type I and II DIB called “type III”. The three DIB types are designed with the main purpose to create three different flow profiles. The influences of DIB height with a single pitch distance (P/D = 1) and DIB attack angle of 30° for heat transfer characteristics and fluid streams are discussed in a laminar flow region at Re = 100–2000 (considered at the entry condition). The numerical problem of the HXT inserted with the DIB is solved with a commercial code (the finite volume method). The computation domain is validated to confirm the reliability and accuracy of the simulated results. The flow configurations: streamlines in transverse planes (y-z planes), and heat transfer behaviors: temperature contours in transverse planes (y-z planes) and local Nusselt number contours (Nux), in the HXT equipped with the DIB are proposed in the simulated-result section. The relations of the average Nusselt number ratio (Nu/Nu0), friction factor ratio (f/f0) and thermal enhancement factor (TEF) with the Reynolds numbers in the HXT inserted with the DIB are presented. As the simulated results, the equipment of the DIB in the HXT brings upper heat transfer rate and thermal performance than those of the smooth tube because of the creations of the vortex streams and impinging streams. The different flow profiles are detected when varying the DIB types that impact for the variations of the heat transfer profile. For the studied range, the increased heat transfer rate in the HXT installed with the DIB is observed to be around 1.03–17.46 times above the plain tube depended on the DIB type, DIB blockage and Reynolds number. Additionally, the maximal TEF of 3.70 is found for the type II DIB at b/D = 0.25 and Re = 2000.
Keywords: Dual-inclined baffle; Heat exchanger; Heat transfer enhancement; Thermal performance; Vortex generator